Study of [Pb(II) and Cd(II)-Malonate-triazole] System as a Tool in The Removal of Excess Lead and Cadmium from Human Blood : A Polarographic Approach - Paliwal, R.K. (Asian Journal of Chemistry, 2010)
This paper is mainly focusing on this aspect that the simple and mixed complexes of Pb and Cd with malonate (mal) and triazole (Tr) are soluble and stable and hence may be excreted through urine. The stability constants of soluble mixed ligand complexes [Pb(mal) (Tr)] (Cd(mal) Tr], [Pb(mal) (Tr)2], [Cd(mal) (Tr)2], [Pb(mal)2(Tr)]2-, [Cd(mal)2 Tr]2- are log β11 = 3.01, 1.698, log β12 = 3.79, 3.176, log β21 = 4.97] 3.146, respectively at the pH of human blood i.e. at 7.4. The values of stability constant is determined polarographically.